1993
DOI: 10.1007/bf00315391
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and haemodynamic effects of a single oral dose of the novel ACE inhibitor spirapril in patients with chronic liver disease

Abstract: The pharmacokinetics and haemodynamic effects of orally administered spirapril, a novel angiotensin-converting enzyme (ACE) inhibitor, have been investigated in patients with liver cirrhosis (n = 10), in patients with chronic, non-cirrhotic liver disease (n = 8) and in a control group of healthy subjects (n = 16). The absorption and elimination of spirapril did not differ between patients with liver disease and control subjects. In contrast, the bioavailability of spiraprilat, the metabolite responsible for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…Similar correlations have also been described in previous studies of drug-disposition in patients with cirrhosis [41]. Since they could not be described by a linear mathematical function (as was the case for SBA concentration), however, they cannot be used to extrapolate dosing recommendations for propranolol in patients with liver cirrhosis.…”
Section: Discussionsupporting
confidence: 70%
“…Similar correlations have also been described in previous studies of drug-disposition in patients with cirrhosis [41]. Since they could not be described by a linear mathematical function (as was the case for SBA concentration), however, they cannot be used to extrapolate dosing recommendations for propranolol in patients with liver cirrhosis.…”
Section: Discussionsupporting
confidence: 70%
“…[78] Studies of enalapril and spirapril showed a prolonged elimination half-life for the diacid, consistent with a reduction in clearance. [68,77] This would suggest that, with these drugs, inhibition of the conversion of prodrug to diacid may be compensated by reduced clearance of the diacid metabolite formed. Equally, without an alternative elimination pathway, it may be that only the rate and not the extent of formation of the diacid is reduced, and that its elimination is unchanged.…”
Section: Prodrug Metabolismmentioning
confidence: 97%
“…The authors concluded that the measured serum creatinine level was inaccurate in predicting GFR in cirrhosis because of reduced muscle mass and reduced conversion of creatine to creatinine resulting from hepatic impairment. The calculated creatinine clearance, which uses the serum creatinine level, was also inaccurate in predicting GFR 600 (68) 381 because of use in the nomogram of body weight that was likely to be inflated due to the presence of ascites. The measured creatinine clearance was inaccurate because of an increased fractional tubular secretion of creatinine as the GFR deteriorated.l'<'…”
Section: Creatinine Clearance As a Marker Of Renal Function In Liver mentioning
confidence: 98%
See 2 more Smart Citations